A STUDY ON WEED CONTROL IN SOYBEAN - S. TJITROSEMITO (SEAMEO BIOTROP, 1991)
Two field experiments on weed control in soybeans were carried out at BIOTROP, Bogor, Indonesia from February to June, 1989. The critical period for weed control was found to be between 20 - 40 days after planting of soybean (c. v. Wilis) grown at a planting distance of 40 x 10 cm. It did not coincide with the fastest growth in terms of trifoliate leaf number. Further studies were suggested to understand the physiological growth of soybean related to weed control. Pendimethalin at 660- 1320 g a.e./ha applied one day after sowing did not cause any phytotoxic effect to soybean and had good weed control performance.